A resilience assessment method for urban water systems. Issue 4 (21st April 2018) - Makropoulos, C.; Nikolopoulos, D.; Palmen, L.; Kools, S.; Segrave, A.; Vries, D.; Koop, S.; van Alphen, H. J.; Vonk, E.; van Thienen, P.; Rozos, E.; Medema, G.
ABSTRACT: Infrastructure planning for Urban Water Systems (UWSs) is challenged by, inter alia, increasing uncertainty in both demand and availability of water and aging infrastructure, and this is already impacting the climate-proofing of cities. In this context, the idea of resilience has been gradually embraced by the water sector, but the term itself is not yet universally defined, nor operationalised. Here, we propose a methodology to assess the resilience of a UWS, defining it as the degree to which the UWS continues to perform under increasing stress. A resilience assessment method is then proposed as a 'stress-test' of UWS configurations, under increasingly more stressful scenarios. We then demonstrate a toolbox assembled for the proposed analysis using, as a proof of concept, a semi-synthetic case study. Results are promising, suggesting that the approach could assist in the uptake and evolution of resilience thinking in strategic water infrastructure decision making, leading to water-wiser cities.